The Enchanted Wood - Enid Blyton
About the Book: Enchanted Wood: The Faraway Tree When Joe, Beth and Frannie move to a new home, an Enchanted Wood is on their doorstep. And when they discover the Faraway Tree, that is the beginning of many magical adventures. Will it be the Land of Spells, the Land of Treats, or the Land of Do-As-You-Please? "I expect I shall find it rather dull here after living in London. It seems so quiet. I shall miss the noise of buses and trams." When Joe, Beth and Frannie move to a new home, an Enchanted Wood is on their doorstep. And when they discover the Faraway Tree, that is the beginning of many magical adventures! Join them and their friends Moonface, Saucepan Man and Silky the fairy as they discover which new land is at the top of the Faraway Tree. Will it be the Land of Spells, the Land of Treats, or the Land of Do-As-You-Please unk This is the first book in Enid Blytons Faraway Tree series. First published in 1939, this has become a true classic, from the author of The Famous Five, The Wishing Chair and The Secret Seven. "One of Britains best-loved childrens authors".